1998
DOI: 10.1086/300611
|View full text |Cite
|
Sign up to set email alerts
|

A Photometric and Kinematic Study of AWM 7

Abstract: We have measured redshifts and Kron-Cousins R-band magnitudes for a sample of galaxies in the poor cluster AWM 7. We have measured redshifts for 172 galaxies; 106 of these are cluster members. We determine the luminosity function from a photometric survey of the central 1.2 h^{-1} x 1.2 h^{-1} Mpc. The LF has a bump at the bright end and a faint-end slope of \alpha = -1.37+-0.16, populated almost exclusively by absorption-line galaxies. The cluster velocity dispersion is lower in the core (\sim 530 km/s) t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 66 publications
6
17
0
Order By: Relevance
“…It can be seen that one point in particular is very high on this relation: the poor cluster AWM 7 has (M/L B J ) ∼ 1600 (M/L B J ) , albeit with rather large errors. A large mass-to-light ratio was also measured for this system by Koranyi et al (1998), who found a value for the R band of (650 ± 150) h 100 (M/L) , corresponding to (830 ± 190) h 70 (M/L B J ) , consistent with our 1σ lower bound of ∼650. Exclusion of this point lowers the mean of our sample from 318 ± 52 to 276 ± 32 h 70 (M/L B J ) .…”
Section: Mass-to-light Ratiosupporting
confidence: 90%
“…It can be seen that one point in particular is very high on this relation: the poor cluster AWM 7 has (M/L B J ) ∼ 1600 (M/L B J ) , albeit with rather large errors. A large mass-to-light ratio was also measured for this system by Koranyi et al (1998), who found a value for the R band of (650 ± 150) h 100 (M/L) , corresponding to (830 ± 190) h 70 (M/L B J ) , consistent with our 1σ lower bound of ∼650. Exclusion of this point lowers the mean of our sample from 318 ± 52 to 276 ± 32 h 70 (M/L B J ) .…”
Section: Mass-to-light Ratiosupporting
confidence: 90%
“…Bright galaxies come from large haloes ( M 200 >10 13 h −1 M ⊙ , long‐dashed and short‐dashed lines). Note that these haloes show a slight bump in the luminosity function at M B −5 log h ∼−20.5 and −22, similar to the bump in the luminosity function of several real clusters (see, e.g., Molinari et al 1998, Trentham 1998 and Koranyi et al 1998) including Coma (Biviano et al 1995). In the models, this effect originates from the large merger cross‐section of the bright and massive central galaxies, which tend preferentially to accrete galaxies of somewhat lower mass.…”
Section: Groups In Real Spacesupporting
confidence: 62%
“…Unfortunately, it is still relatively uncommon to see this correction applied (see, e.g., Koranyi et al 1998). Neglecting this correction leads to overestimate the mass of a system (see, e.g., Carlberg et al 1997a), and this can partly account for some of the claimed discrepancies between optically and X-ray derived cluster mass estimates.…”
Section: The Cluster Mass Estimatesmentioning
confidence: 99%